Intellectual property, tariffs, and international trade dynamics - Federico S. Mandelman; Andrea Waddle (Federal Reserve Bank of Atlanta, 2019)
The emergence of global value chains not only leads to a magnification of trade in intermediate inputs but also to an extensive technology diffusion among the different production units involved in arms-length relationships. In this context, the lack of enforcement of intellectual property rights has recently become a highly controversial subject of debate in the context of the China-U.S. trade negotiations. This paper analyzes the strategic interaction of tariff policies and the enforcement of intellectual property rights within a quantitative general equilibrium framework. Results indicate that, in principle, tariffs could be an effective deterrent for weak protections for intellectual property. Moreover, weakening enforcement may be a strong deterrent for raising tariffs. These results combined indicate that there is scope for international cooperation on these fronts.
Keywords: F41; F42; F51; F21; F13; 330; tariffs; intellectual property rights; technology capital transfers; international trade